Peculiarities of Hydrogen Production Technology Using Energy Storage Materials - Kozin, L.F.; Volkov, S.V.; Sviatogor, A.V.; Daniltsev, B.I. (Science and Innovation, 2024)
The paper presents information about the possibility to produce high-purity hydrogen on a pilot and pilot-industrial scale (1000 m3 H2/hour) using energy storage materials and gives some peculiarities of this technology.